Análisis del rol del comunicador social frente a la pandemia. Casos graduados UTB 2018-2020 - Mora Álvarez, Dayana (2020)
A point of view is raised regarding the devices that are used by social communicators in the face of the pandemic. UTB 2018-2020 graduate cases to fit into the labor market, therefore, there are certain demands and problems that they risk. Currently the chances of finding jobs have been reduced due to the situation that the whole world is going through, such as Covid19, ruling out that they increasingly require requirements such as work experience, higher education since generally the owners of the companies demand such a requirement. Not according to the number of workers hired has nothing to do with the amount of work spaces, since the following title is not taken into account due to the demands in the workplace. Losing your job in the midst of this crisis can generate increased anxiety and stress, therefore graduates of Communication Sciences are not free from this situation.